Hedonic and eudaimonic well-being in old age through positive psychology studies: a scoping review - Araujo, Lia; Ribeiro, Oscar; Paúl, Constança (Anales de Psicología / Annals of Psychology, 2017)
The study of aging through the lens of Positive Psychology allows looking beyond the decline normally associated with advancing of age and to consider rewarding experiences and strategies to promote a meaningful aging. In order to gather evidence on the key conceptual and empirical advancements that illustrate the commitment of Positive Psychology with aging issues a scoping review was conducted. Papers having “Positive Psychology” AND “Aging” (or similar words to aging) on their title, abstract or key-words were screened across main databases and aging related terms were searched in well-known journals of positive psychology. This strategy yielded 48 articles, 33 original scientific papers and 15 reviews. Main themes, study designs and instruments are presented and the endpoints are discussed according to the hedonic or eudaimonic perspective of the studies. Future directions related with the importance of comprehensive constructs and method approaches in the study of advancing age are highlighted.